The Influence of Digital-Based Gamification on Student Engagement and Language Literacy Skills: A Study at Madrasah Tsanawiyah - Ariani, Farida; Afnita, Nora (Jurnal Komunikasi Pendidikan, 2024)
The advancement of technology in education has revolutionized the learning process, transitioning from conventional to digital systems. Technology-based learning addresses the challenge of limited learning time for active students. Digital-based gamification for language learning in schools is a recent development, streamlining the teaching and learning process and enhancing outcomes. This study aims to assess the effectiveness of digital-based gamification models on the engagement and language literacy skills of eighth-grade students at Madrasah Tsanawiyah in Pariaman City. Using a quasi-experimental approach with a 2x3 factorial design, the study employs the Student Engagement in Schools Questionnaire and a Language Literacy Learning Outcomes Test as research instruments. Results indicate differences in student engagement between gamification and conventional models and between high and low-engagement groups. Interaction effects between gamification and engagement levels on language and literacy ability were observed. Overall, the gamification model proved more effective than conventional methods in enhancing engagement and learning outcomes. It is recommended that the Principal of the Madrasah implement digital-based gamification models tailored to students' needs to enhance engagement and learning outcomes.